2008
DOI: 10.1055/s-2008-1081342
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids fromIris songaricaand their Antioxidant and Estrogenic Activity

Abstract: A new dihydroflavonol, songaricol ( 1) and seven known flavonoids, ayamenin A ( 2), irisflavone A ( 3), 5,7-dihydroxy-2',6-dimethoxyisoflavone ( 4), irilin B ( 5), 5,3'-dihydroxy-7,8,2'-trimethoxyisoflavone ( 6) and irisoid A ( 7) were isolated from rhizome and roots of IRIS SONGARICA. Structure elucidation of 1 was achieved through extensive NMR and circular dichroism techniques. Compounds 1, 5 and 7 showed antioxidant activity in HL-60 cells (IC50 values of 21, 11 and 3.8 microg/mL), whereas 2, 5 and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
(16 reference statements)
1
19
0
Order By: Relevance
“…13 C-NMR (CD 3 OD) δ: 181.2 (C-4), 157.4 (C-2′), 154.2 (C-7), 153.8 (C-2), 153.6 (C-5), 153.2 (C-9), 131.4 (C-6), 130.0 (C-6′), 122.8 (C-4′), 121.9 (C-3), 121.5 (C-1′), 114.5 (C-5′), 109.8 (C-3′), 105.3 (C-10), 93.6 (C-8), 59.5 (6-OCH 3 ), 55.1 (7-OCH 3 ). The above data were identical to the literature data [21].…”
Section: Methodssupporting
confidence: 87%
“…13 C-NMR (CD 3 OD) δ: 181.2 (C-4), 157.4 (C-2′), 154.2 (C-7), 153.8 (C-2), 153.6 (C-5), 153.2 (C-9), 131.4 (C-6), 130.0 (C-6′), 122.8 (C-4′), 121.9 (C-3), 121.5 (C-1′), 114.5 (C-5′), 109.8 (C-3′), 105.3 (C-10), 93.6 (C-8), 59.5 (6-OCH 3 ), 55.1 (7-OCH 3 ). The above data were identical to the literature data [21].…”
Section: Methodssupporting
confidence: 87%
“…Dihydroflavonol, songaricol (78) from I. songarica, show antioxidant activity. 137 Some isoflavonoids, irigenin (169) and its 7-Oglucoside, 163 irilin B (95), 137 irolone (111) 4′-Oglucoside, 136 irisflorentin (146), 163 iristectorigenin A (152) and its 7-Oglucoside, iristectorigenin B (154) 7-Oglucoside, 163 5,6,7,3′-tetrahydroxy-4′-methoxyisoflavone (140), 194 and tectorigenin (163) 194 and its 7-Oglucoside, 163,194 were proved to have antioxidant activity. Similarly, 6 isoflavonoids, 163 and its 7-Oglucoside, daidzein (100), genistein (158), and formononetin (125) from I. aphylla show antibacterial activity in Gram-positive bacteria and fungi.…”
Section: Activities and Functions Of Flavonoids And Xanthones In Iris Speciesmentioning
confidence: 99%
“…139 Three isoflavonoids, ayamenin A (101), irisone B (110), and 95, were proved to have estrogenic activity in yeast cells expressing human estrogen receptor. 137 Estrogen receptor modulator activity was shown in 163 from I. domestica. 92 As anticancer and antitumor activities, 3 isoflavonoids, 169, 111, and iriskashmirianin (124), have cancer chemoprevention activity.…”
Section: Activities and Functions Of Flavonoids And Xanthones In Iris Speciesmentioning
confidence: 99%
“…indicated that the plants contain several classes of secondary metabolites such as flavonoids, isoflavones, and their glycosides, C -glucosylxanthones, quinones, triterpenoids, and stilbene glycosides [ 12 , 13 , 14 ]. These compounds contribute to the observed immunomodulatory [ 15 , 16 ], estrogenic [ 17 , 18 ], antioxidative [ 19 , 20 , 21 ], antibacterial [ 22 , 23 ] and anticholinesterase [ 24 ], cytotoxic [ 11 , 25 ], and anti-osteoporotic activities [ 26 ]. Experimental results indicate a direct correlation between Iris phenolic compounds (hydroxycinnamic acids, isoflavones, flavones, xanthones) and their pharmacological activity, especially the antioxidant activity [ 20 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%